KONFLIK PEMERINTAH ACEH DAN PEMERINTAH PUSAT PASCA MOU HELSINKI : SELF-GOVERNMENT - BASRI, HASAN (Program Magister Ilmu Politik, Universitas Diponegoro, 2014)
After the signing of Helsinki MoU between GAM and the Republic of Indonesia, Aceh started running the the Law on Governing Aceh, which is the implementation of an Helsinki MoU agreement. Aceh's provincial parliament political elite which the majority of both ex-combatants want to make Aceh a self-government (self-government) which has occurred in Aceh. But do not actually done by a political elite which led to the central limit the authority of Aceh Aceh. Aceh Government continues to urge of the Central Government to yourself Gavernment in Aceh. This is unlikely to happen, as opposed to the constitution. Center only give special autonomy similar to which previously granted to Aceh Indonesia. This conflict occurs between of the Central Government and the Government of Aceh.